2021
DOI: 10.3390/mps4040081
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Carried Ultrasonography Instrumentation in the Diagnosis of Temporomandibular Joint Dysfunction

Abstract: Internal derangement (ID) in the temporomandibular joint (TMJ) is defined as a mechanical problem of the joint that interferes with its function. It is attributed to an abnormal interaction among the articular disc, condyle, and joint eminence. The aim of this study is to evaluate diagnostic efficacy of non-invasive hand-carried ultrasonography instrumentation (US) to provide high-level images for a correct diagnosis of ID. Twenty-eight ID patients, 15 female and 13 males, were examined both clinically and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Similar results were found in other studies ( 77 ), and in particular, following progressive employment of transducer with higher frequency, of 10 MHz or more, allow a better sensitivity, ranging from 60% to 90% ( 30 , 40 , 42 , 45 ). Specifically, a recent review ( 28 ) found that high-resolution US (HR-US), defined as a US resolution of 12 MHz or more, improves sensitivity and specificity in the detection of TMJ involvement as compared to low-resolution US (LR-US), defined as a US resolution of <12 MHz ( 28 , 31 ).…”
Section: Methodssupporting
confidence: 90%
“…Similar results were found in other studies ( 77 ), and in particular, following progressive employment of transducer with higher frequency, of 10 MHz or more, allow a better sensitivity, ranging from 60% to 90% ( 30 , 40 , 42 , 45 ). Specifically, a recent review ( 28 ) found that high-resolution US (HR-US), defined as a US resolution of 12 MHz or more, improves sensitivity and specificity in the detection of TMJ involvement as compared to low-resolution US (LR-US), defined as a US resolution of <12 MHz ( 28 , 31 ).…”
Section: Methodssupporting
confidence: 90%
“…The disc position was not checked in any of the included studies probably because previous outcomes on patients with TMD were confusing. Only a few authors observed some abnormalities in the disc‐condyle relationship through US, 43,51–55 however, it is overall accepted that US is not useful neither accurate to diagnose TMJ disc displacements 36,43,56–60 when a discrimination between displacement with or without reduction is needed 43,54 …”
Section: Discussionmentioning
confidence: 99%
“…36,46 The disc position was not checked in any of the included studies probably because previous outcomes on patients with TMD were confusing. Only a few authors observed some abnormalities in the disc-condyle relationship through US, 43,[51][52][53][54][55] however, it is overall accepted that US is not useful neither accurate to diagnose TMJ disc displacements 36,43,[56][57][58][59][60] when a discrimination between displacement with or without reduction is needed. 43,54 About the detection of intraarticular effusion in the TMJ area, Manfredini et al 54 stated that US remains potentially useful as an alternative imaging technique with a good accuracy, 48 even though the challenging analysis of TMJ capsular width is in only 2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging is the gold standard for diagnosis and treatment planning in the disorders of articular disk. 22,23 With the use of MRI, examinations are performed with closed and opened mouth, and mostly static images are taken with an uncomfortable and expensive instrument. Ultrasound (US) examinations overcome these limitations.…”
Section: Discussionmentioning
confidence: 99%